Sexual selection moderates heat stress response in males and females. (27th October 2022) - Moiron, Maria; Winkler, Lennart; Martin, Oliver Yves; Janicke, Tim
Abstract: A widespread effect of climate change is the displacement of organisms from their thermal optima. The associated thermal stress imposed by climate change has been argued to have a particularly strong impact on male reproduction but evidence for this postulated sex‐specific stress response is equivocal. One important factor that may explain intra‐ and interspecific variation in stress responses is sexual selection, which is predicted to magnify negative effects of stress. Nevertheless, empirical studies exploring the interplay of sexual selection and heat stress are still scarce. We tested experimentally for an interaction between sexual selection and thermal stress in the red flour beetle Tribolium castaneum by contrasting heat responses in male and female reproductive success between enforced monogamy and polygamy. We found that polygamy magnifies detrimental effects of heat stress in males but relaxes the observed negative effects in females. Our results suggest that sexual selection can reverse sex differences in thermal sensitivity, and may therefore alter sex‐specific selection on alleles associated with heat tolerance. Assuming that sexual selection and natural selection are aligned to favour the same genetic variants under environmental stress, our findings support the idea that sexual selection on males may promote the adaptation to current global warming. Read the free Plain Language Summary for this article on the Journal blog. Abstract : Read the free Plain Language Summary for this article on the Journal blog.